Effect of Formula Endophytic Bacteria in Organic Fertilizer to Wilt Disease Fusarium in Chili Plants - Laras Setyowati; Arika Purnawati; Tri Mujoko (Future Science, 2022)
Chili (Capsicum annum) is one of the horticultural commodities that has an important role in human life and Indonesian chili plants have important economic value and occupy second place after beans. Meanwhile, in East Java, chili commodity production in 2013-2017 reached 440 tons and one of the highest contributors was Ringinsari, Kandat, Kediri. However, the increase in chili commodities in the village has so far been strongly influenced by the presence of the fungi pathogen is Fusarium oxysporum f.sp.capsici that cause wilt disease, can reduce production on average up to 75 % and cause the plant to die. The control of that pathogen generally uses chemical control that hurts humans and the environment so until now it have not been satisfactory. Depend of that it needs alternative control using endophytic bacteria that are formulated in organic fertilizer as biological control. Endophytic bacteria are group of bacteria that live in plant tissues without causing negative effects, including not causing plants to get sick and having a mutual relationship with their host plants. Endophytic bacteria can be found in various plants including agricultural crops and can be isolated from all parts of the plant, namely roots, stems, leaves, and seeds. Endophytic bacteria produce secondary metabolites and compounds that can be used to induce plant health and growth. Endophytic bacteria produce fenol, flavonoid that increase plant resistance to diseases and pests, improve plant health, phytohormones increase plant growth. The method stages of research are propagation of endophytic bacteria, manufacture of suspension of endophytic bacteria, mixing of suspension of endophytic bacteria into organic fertilizer, data analysis using analysis of variance and 5% BNT test. The results are Incubation period is slower, disease intensity decreases, and plant height increases.